Genome editing, a superior therapy for inherited retinal diseases. (May 2023) - Yan, Alexander L.; Du, Samuel W.; Palczewski, Krzysztof
Graphical abstract: Highlights: Limitations of current gene augmentation therapies need to be addressed. Advances in CRISPR-Cas9 systems have potential to treat inherited retinal diseases. Base editing and prime editing enable precise mutation corrections in the eye. Advances in delivery methods have improved safe, effective precision gene editing. Delivery of ribonucleoproteins or mRNA is ideal for therapeutic CRISPR treatments. Abstract: Gene augmentation and genome editing are promising strategies for the treatment of monogenic inherited retinal diseases. Although gene augmentation treatments are commercially available for inherited retinal diseases, there are many shortcomings that need to be addressed, like progressive retinal degeneration and diminishing efficacy over time. Innovative CRISPR-Cas9-based genome editing technologies have broadened the proportion of treatable genetic disorders and can greatly improve or complement treatment outcomes from gene augmentation. Progress in this relatively new field involves the development of therapeutics including gene disruption, ablate-and-replace strategies, and precision gene correction techniques, such as base editing and prime editing. By making direct edits to endogenous DNA, genome editing theoretically guarantees permanent gene correction and long-lasting treatment effects. Improvements to delivery modalities aimed at limiting persistent gene editor activity have displayed an improved safety profile and minimal off-target editing. Continued progress to advance precise gene correction and associated delivery strategies will establish genome editing as the preferred treatment for genetic retinal disorders. This commentary describes the applications, strengths, and drawbacks of conventional gene augmentation approaches, recent advances in precise genome editing in the retina, and promising preclinical strategies to facilitate the use of robust genome editing therapies in human patients.